ANALISIS TATA KELOLA TEKNOLOGI INFORMASI DI SANGGAR TARI ABC MENGGUNAKAN COBIT 4.1 - Tikaridha Hardiani; Nurul Latifah (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
Information technology governance is a branch of corporate governance that focuses on information technology (IT) systems and their performance and risk management. The application of information technology in the ABC Dance Studio is currently still limited. The system that has been used at ABC Dance Studio is very limited and there is almost no special application for managing operational processes. ABC Dance Studio has subscribed to cloud computing, namely WD Digital as a back-up storage media and as a server if data is needed at any time. COBIT 4.1 was chosen to determine the maturity level of information technology governance carried out at the ABC Dance Studio and what targets will be achieved to improve the quality of its governance. The results obtained that the level of governance maturity at ABC Dance Studio is currently at level 2 and for the target to be achieved at level 4 maturity, increasing the maturity level to the target must go through level 3 first before reaching the goal level. Recommendations for increasing the maturity of governance are also given to raise the level.